Сиркові пасти із зерновими інгредієнтами - Онопрійчук, Олена Олександрівна; Грек, Олена Вікторівна (My University, 2012)
Визначено амінокислотний склад паст сиркових із зерновими інгредієнтами і збалансованість амінокислотного складу білків. Введення зернових інгредієнтів в певній кількості в молочну основу дозволяє замінити частину білка тваринного походження рослинним, не погіршуючи при цьому якість готових продуктів. Розроблені сиркові пасти із зерновими інгредієнтами мають підвищену біологічну цінність у порівнянні з традиційними, володіють дієтичними і профілактичними властивостями за рахунок харчових волокон, макро- і мікроелементів, розширюють асортимент продуктів на молочно-білковій основі. Amino acid composition of curd pastes with grain-growing ingredients and equilibrium of amino acid composition of proteins are determined. Herewith, the properties of Amino acid composition of animal and vegetable proteins and degree of assimilation after digestion were considered. Amino acid composition was determined by ion exchange chromatography on an automatic analyzer of amino acids Т 339, of "Mikrotehna" (Czech Republic). To assess the degree of protein was determined an amino acid score – the average of excess of amino acid score of essential amino acids compared with the limiting amino score. There was estimated the level of the mutually balanced essential and nonessential amino acids protein product. The correlative dependence between the biological value of protein and its amino acid composition was determined by studying protein attachment in vitro with complex of proteolytic enzymes - pepsin and trypsin. So, introduction the certain amount of grain-growing ingredients into milk basis allows to replace part of animal origin albumen with vegetable, not worsening quality of the prepared foods. The worked out curd pastes with grain-growing ingredients have an enhance able biological value as compared to traditional, possess dietary and prophylactic properties due to food fibers, macro- and micro elements, extend the assortment of foods on milk-albuminous basis.
Keywords: пасти сиркові; curd pastes; зернові інгредієнти; grain-growing ingredients; амінокислотний склад; amino acid composition; біологічна цінність; biological value; коефіцієнт різниці амінокислотного скора; amino acid score; кафедра технології молока і молочних продуктів